EFEKTIVITAS METODE PEMBELAJARAN DARING PADA MAHASISWA PENDIDIKAN AGAMA ISLAM SEKOLAH TINGGI AGAMA ISLAM JAM’IYAH MAHMUDIYAH - Marhan Hasibuan (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2021)
This study aims to determine the effectiveness of online learning in the system approach course in learning in the Covid-19 pandemic situation in the Islamic religious education study program of the Jam'iyah Mahmudiyah Islamic Religion College in Tanjung Pura. This research is also to evaluate the quality of online learning that has been implemented and as a material for developing an online learning system in the new normal era. The research method used is quantitative with a survey method. The number of samples in this study were 150 students. Retrieval of data using a survey method with a Likert scale. Data analysis by calculating the percentage of data on each indicator, then interpreted the data percentage score and analyzed descriptively on each indicator. The results showed that the effectiveness of online learning in the system approach course in learning in the Covid-19 pandemic situation in the Islamic religious education study program of the Jam'iyah Mahmudiyah Islamic School of Tanjung Pura reached 74% or was in the good category. The results of this study are also expected to become a reference in the development of online learning in tertiary institutions and as study material for further research related to the effectiveness of online learning.